Motyw zwycięskiej modlitwy w narracji Joz 10,1-27 - Jasiński, Mirosław (Verbum Vitae, 2012)
Taking the subject of “victorious prayer”, author shows in detail the literary structure of the pericope Josh 10:1-27, and draws attention that the central point of the story is verse 14a: “There was no day like that before it or after it, when the Lord listened to the voice of a man”. These words, according to the author, are important hagiograph’s indication for the proper reading of the entire pericope’s message. After analyzing the main literary issue of the story, the article presents hallmarks and fruits of the “victorious prayer” of Joshua. As motivated by trust, backed by commitment and consistent with God’s plan, resulted in a deepening Joshua’s ties with the Lord, strengthen authority both of them and complete victory over a coalition of Canaanite kings. Author suggests that “the day of Joshua” described in Josh 10:1-27, later became for the biblical authors, a kind of model using to description of the “day of the Lord”. Recognizing the pericope as “praeparatio evangelica remota”, author encourages to typological interpretation of the Book of Joshua.